CLASIFICACIÓN DE LA MALOCLUSIÓN SEGÚN ANGLE EN EL PERÚ (Análisis de 27 trabajos de investigación). - Menéndez Méndez, Leoncio Wadimir (1998)
This present article is a revision of 27 Bachelor Tesis in Odontology (UNMSM, UPCH). Everyone made the investigation in the incidence of malocclusion of the different departments of the country (La Libertad, Puno Huanuco, Cerro de Pasco, Cajamarca y Ancash). Its context permits partial panoramic views of the malocclusions in Peru. The principal characteristics coincide with a porcentage in the following order: Normal oclussions, Class I, Class II y Class III.